HERITAGE HOTELS AS NATIONAL MONUMENTS: AN EXAMINATION OF THE CONSERVATION AND PROMOTIONAL NARRATIVES OF COLONIAL HERITAGE HOTELS IN SINGAPORE SINCE THE 1980S - CHUNG XIAO XUAN GLORIA (2019)
Bachelor's